Analysis of electromigration failure of nano-interconnects through a combination of modeling and experimental methods. (September 2019) - Ceric, H.; Zahedmanesh, H.; Croes, K.
Abstract: Electromigration assessment and optimization of nano-interconnects is a complex task which ultimately demands an application of both experimental and modeling methods. The goal of this work is to introduce and discuss a modeling concept that is not unnecessarily complex and that can be optimally combined with experimental studies in order to assess the relative impact of different factors on interconnect reliability. The presented model and related modeling methodology are applied to a set of electromigration tests.